Climate warming negates arbuscular mycorrhizal fungal reductions in soil phosphorus leaching with tall fescue but not lucerne. (January 2021) - Zhang, Haiyang; Powell, Jeff R.; Plett, Jonathan M.; Churchill, Amber C.; Power, Sally A.; Macdonald, Catriona A.; Jacob, Vinod; Kim, Gil Won; Pendall, Elise; Tissue, David; Catunda, Karen M.; Igwenagu, Chioma; et al.
Abstract: Nutrient losses due to leaching from agricultural soils can be substantial but, in some cases, soil microbes such as arbuscular mycorrhizal (AM) fungi can buffer those losses. An important knowledge gap, however, is the extent to which climate change may affect AM fungal mediation of leaching via warming and drought. To investigate this, we grew lucerne ( Medicago sativa ) and tall fescue ( Festuca arundinacea ), in the presence and absence of AM fungal inoculation ( Rhizophagus irregularis ), under different temperature [ambient: 26 °C (aT); elevated: 30 °C (eT)] and water [well-watered: 100% soil water holding capacity (WHC); droughted: 40% WHC] treatments. After four months of plant growth, leached nutrients (PO4 −, NH4 + and NO3 − ), plant biomass, nitrogen (N), phosphorus (P), and mycorrhizal parameters (colonization and extraradical hyphae biomass) were measured. The presence of AM fungi significantly reduced P leaching with lucerne by 46% for both temperature treatments, but P loss with tall fescue was only reduced under aT (by 48%). The negation of this benefit for tall fescue under eT was associated with a reduction in mycorrhizal root colonization, while temperature did not alter mycorrhizal root colonization of lucerne. Watering regime was not observed to influence P loss via leaching. We did not find a mycorrhizal effect on N leaching for either species; however, we found that N leaching increased under drought with lucerne and responded interactively to warming and drought with tall fescue. Overall, AM fungi significantly reduced P leaching for both species, but warming eliminated this effect for tall fescue, suggesting that warming may differentially affect P leaching depending upon plant species. Highlights: AM fungi reduce P leaching for the pastures under ambient temperature. AM fungi still reduce P leaching for lucerne but not for tall fescue under warming. Root colonization drives the mycorrhizal reduction in P leaching under warming.